ChemInform Abstract: Enantioselective Allylic C—H Oxidation of Terminal Olefins to Isochromans by Palladium(II)/Chiral Sulfoxide Catalysis. Issue 50 (November 2016) - Ammann, Stephen E.; Liu, Wei; White, M. Christina
Abstract: Novel chiral aryl sulfoxide‐oxazoline ligands are synthesized and employed in the enantioselective synthesis of isochromans.